IADT 2020 Guidelines: What should the dental professional know?. Issue 4 (December 2021) - Bennett, Reuben; Loo, Yi; Ilyas, Nabeel
Traumatic dental injuries are a common occurrence among children. Effective acute and long-term management of traumatic dental injuries can improve patient outcomes, especially in the paediatric patient. It is important that all dental professionals follow up-to-date, evidence-based guidance when treating patients. This article aims to highlight the main changes in the 2020 International Association of Dental Traumatology (IADT) Guidelines for Evaluation and Management of Traumatic Dental Injuries, to ensure that all dental professionals are fully aware of current guidelines and are managing patients appropriately.